MA Defence: â€œCommunicating Communes: A Case Study of Urban Communing Movement in South Koreaâ€ By Didi (Kyoung-ae) Han - Chen, Sibo (Stream: Interdisciplinary Journal of Communication, 2015)
Our dear colleague, Didi (Kyoung-ae) Han, will defend her MA Thesis on Monday, September 8th, 2015 at Harbour Centre, Room 2250 (10 am -12 noon). Here is the abstract of her thesis “Communicating Communes: A Case Study of Urban Communing Movement in South Korea”.